2010
DOI: 10.1007/s10535-010-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient regeneration of Eucalyptus urophylla from seedling-derived hypocotyls

Abstract: Seedling hypocotyls were used as explants to establish a regeneration protocol for Eucalyptus urophylla and N-phenyl-N'-[6-(2-chlorobenzothiazol)-yl] urea (PBU), one kind of di-substituted urea, was found useful growth regulator. The hypocotyls incubated on a modified Murashige and Skoog medium (SPCa), supplemented with 6.6 μM PBU and 0.57 μM indole-3-acetic acid (IAA) dedifferentiated and form calli (100 % after 7 d). Compared with other growth regulator combinations, PBU stimulated more vigorous calli and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…After this period, the calluses gradually became brown and no adventitious buds were observed. In a previous study PBU induced higher percentage of callus formation was observed than other plant growth regulators (Huang et al 2010). About 96% of the cut surface had grown calli on the 6th day when the explants were cultured on MS medium containing 13.2 µM PBU and 0.285 µM IAA (Table 1).…”
Section: Callus Formationmentioning
confidence: 79%
“…After this period, the calluses gradually became brown and no adventitious buds were observed. In a previous study PBU induced higher percentage of callus formation was observed than other plant growth regulators (Huang et al 2010). About 96% of the cut surface had grown calli on the 6th day when the explants were cultured on MS medium containing 13.2 µM PBU and 0.285 µM IAA (Table 1).…”
Section: Callus Formationmentioning
confidence: 79%
“…Em Eucalyptus urophylla o comprimento médio das brotações alongadas foi de 25 mm após 40 dias de cultivo in vitro, de ANA e 0,1 mg L -1 de GA 3 (HUANG et al, 2010). Provavelmente, as diferentes espécies e idades das árvores tenham interferido na resposta observada, com o maior alongamento ocorrendo na presença da giberelina.…”
Section: Resultsunclassified
“…However, SP medium [108,[110][111][112], WPM minerals [113], WPM [114], B5 medium [115][116][117], N7 medium [86,118], JADS medium [98], EDM [119], and MS medium with White vitamins [89] have also been used. Callus is often induced in darkness, although basal organogenesis on shoots can occur in eucalypt shoot cultures that are maintained under light [45,46,64,98,120].…”
Section: Organogenesismentioning
confidence: 99%
“…Thidiazuron (TDZ) and 2-Cl-PBU (i.e., 1-phenyl-3-(1,2,3-thiadiazol-5-yl) urea and N-phenyl-N -[6-(2-chlorobenzothiazol)-yl] urea, respectively) are potent promotors of callus formation in eucalypts. Organogenesis can be induced using 0.89 µM BA with 0.91 µM TDZ, or 0.5 µM TDZ with 0.2 µM 2,4-D for E. globulus [127,128], 2 µM TDZ, or 0.23 µM TDZ with 0.05 µM NAA, or 3 µM TDZ with 0.1 µM NAA for E. grandis × E. urophylla [89,123,128], and 2.27 µM TDZ with 0.54 µM NAA, or 1.14 µM 2-Cl-PBU with 0.57 µM IAA for E. urophylla [89,111,112]. Picloram (i.e., 4-Amino-3,5,6-trichloro-2-pyridinecarboxylic acid) has been used alone at 20.7 µM for E. urophylla organogenesis [86] or at 0.04 µM in combination with 2.25 µM BA for E. gunnii Hook.f.…”
Section: Organogenesismentioning
confidence: 99%
See 1 more Smart Citation